Protein Ingredients Control in Gluten Free Products Using SDS-PAGE, Developed Competitive Enzyme Immunoassays and Commercial ELISA Kits. - Cellerino, Karina (2018)
Some protein ingredients declared in the label of gluten free products are allergenic proteins (milk, soy and egg).The proper identification of these proteins in food products is important for consumers who have food allergies. The aim of this study was to control the presence of protein ingredients declared in the label of gluten free products. Samples were analyzed with sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE), using an extractive solution of total proteins (Tris-ClH buffer 0.0625 M with 3% sodium dodecylsulfate and 2% 2-mercaptoethanol; pH: 6.8) and a selective solvent for the extraction of caseins (isopropanol 55° + 2-mercaptoethanol / ISO + ME). Developed Competitive enzyme immunoassays were used for the detection / quantification of milk, soy and egg proteins in products elaborated with rice flour. Specific polyclonal rabbit antiserums against milk, soy and egg proteins were used as primary antibodies in these competitive enzyme immunoassays. Commercial ELISA kits from Neogen, R-Biopharm and Romer were used to verify the results. In some samples undeclared allergens were detected. Correct allergens labeling is very important for the safety of allergic consumers. In conclusion, it is possible to identify all the proteins ingredients in these gluten-free foods studied, using a combination of electrophoretic methods and immunochemical methods.